The role of skin barrier in occupational contact dermatitis - Jakasa, Ivone; Thyssen, Jacob P.; Kezic, Sanja (Experimental dermatology, 2018)
Skin diseases represent one of the most common work‐related diseases and may have a detrimental effect on social, personal and occupational aspects of life. Contact dermatitis (CD), which comprises predominately irritant contact dermatitis (ICD) and allergic contact dermatitis (ACD), accounts for vast majority of occupational skin diseases, especially in occupations associated with frequent skin contact with irritants and contact allergens. Although ICD and ACD have similar clinical manifestation, their pathophysiology and the role of the skin barrier are different. In ICD, perturbation of the skin barrier is the primary event which sets into motion diverse metabolic processes and triggers activation of innate immunity without the involvement of adaptive immune system. In ACD, a type IV hypersensitivity reaction induced by contact allergens, the skin barrier impairment may evoke innate signalling pathways during the sensitization phase required for the activation of T‐cell adaptive response. Thus, skin barrier impairment may increase the risk of ICD or ACD not only because of enhanced permeability and ingress of irritants and allergens but also by the generation of innate immune signal needed for the induction of allergic response. Hence, an efficient way to prevent CD is to avoid skin barrier damage in the workplace. This review focuses on the skin barrier, how it is affected by skin irritants and how its impairment contributes to the development of ICD and ACD.